A Wet Impregnation Strategy for Advanced FeNi‐Based Electrocatalysts towards Oxygen Evolution. Issue 2 (10th December 2020) - Wang, Xueyang; Liu, Yuanjun; Wei, Tiange; Sun, Jinyong; Song, Xuefeng; Chen, Peng; He, Jinghui; Shen, Xiaoping; Zhu, Guoxing
Abstract: In this study, the typical wet impregnation method was employed to prepare advanced electrocatalysts for oxygen evolution reaction (OER). The preparation process is easy‐operation and doesn't require any complex synthesis steps. This strategy was demonstrated with Fe 3+ /Ni 2+ loaded on porous carbon as an example. The thus formed pre‐catalyst was in situ activated in the electrochemical test process, during which the electrochemically active species for OER are achieved. With the optimized catalyst, a current density of 10 mA . cm −2 can be obtained at an overpotential of 275 mV. This catalytic performance is close to or even better than the benchmarked RuO2 and IrO2 catalysts. Especially, the catalyst also exhibits good catalytic stability. This study presents a new non‐chemical synthesis route for advanced oxygen evolution catalysts. Abstract : A simple wet impregnation process was reported for the synthesis of electrocatalysts towards oxygen evolution. During the electrocatalytic process, the impregnated metal ions transform into metal hydroxides or oxyhydroxides acting as catalytic active phase.